The Overview Of Spinal Anesthesia Injection Techniques At RSI Fatimah Cilacap - Baroki Saragih, M.Nuhas; Lintang Suryani, Roro; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2023)
Background: Spinal anesthesia is said to be safer than general anesthesia. However, spinal anesthesia itself has several kinds of special obstacles in performing injection techniques, there are a number complex variables that can cause these obstacles, including difficulty in marking injections, failure in needle placement, age, Body Mass Index (BMI), spinal anatomical abnormalities, patient position at the time of needle placement, and the level of experience of spinal performers. Purpose: This study was to determine the description of spinal anesthesia injection techniques at RSI Fatimah Cilacap. Methods: This research method uses a quantitative approach with a descriptive type of research. Total sampling was used to select the sample for this study. Total sampling is a sampling method that uses the sample size of the entire population as the sample size. Results: this study indicate that the median injection technique is more dominant in using the median injection technique with the number of respondents as many as 23 (62.1%), while with the paramedian injection technique only 14 (37.8%) respondents based on the age of the respondent, while based on the BMI of the respondent, anesthesia stylists are more dominant in using the median injection technique as many as 23 (62.1%) respondents, on the contrary with the paramedian injection technique as many as 14 (37.8%) respondents. Conclusions: this study shows that anesthesiologists at RSI Fatimah Cilacap more often use spinal anesthesia injection techniques with median techniques compared to paramedian injection techniques at certain ages and Body Mass Indexes.